A Social Perspective on Couples Across the Lifespan: Challenges and Opportunities. Issue 4 (1st October 2020) - Rauer, Amy; Proulx, Christine M.
Abstract : Across the life course, individuals are embedded in multiple relationships that have considerable influence on development and well-being. This special issue uses diverse samples and methodologies to disentangle the effects of these ties on individuals and couples, while acknowledging how often different relationships intersect and the consequences of this overlap. This issue includes four articles that begin with a consideration of the influences intimate partners have on each other and then broaden to provide compelling evidence that intimate relationships themselves are not impervious to the influence of outside others. Overall, these studies suggest that a myopic view of intimate relationships as the only ones worth examining in adulthood will not allow a full understanding of adult development and health. Instead, these studies argue that future research on adults' close relationships must be more closely attuned to the broader social environments adults inhabit, with an emphasis on a greater understanding of the health factors that might be most closely tied to relationship functioning at various points across the life course.